How to Combine Student Science Education with Modern Environmental Education - Andrii Chepok; Natalia Yevtushenko (Vasyl Stefanyk Precarpathian National University, 2022)
This work is devoted to current problems of modern education: the formation and  development of scientific thinking of the individual from the school age and the improvement of environmental education of students both of high school and older ones, since the authors do believe that these issues are interrelated. In this paper, some issues of students' scientific education are considered from the standpoint of strengthening the science intensity of the proposed educational content. The authors, being in the systems of secondary and higher schools and based on their own professional experience, found their way to improve the level of scientific education of students by involving them in educational environmental/bionic research works in the form of IT projects. The students' work on such a project implies the main stages of modern researching - from mathematical modeling of a selected natural phenomenon to mathematical processing of the corresponding computer experiment results and their interpretation. The organization of training-and-research activities of high school students and working on such researches have several positive outcomes, one of which is not only the improvement of knowledge in the Natural sciences, but also other positive aspects related to certain types of human thinking - critical, algorithmic, logical and creative ones. The authors believe that significant success in conducting student research can be achieved by working with "ordinary-and-average" but motivated students. The authors prove with their practical experience that it is possible to identify and educate young people with qualities (maybe with talents!) of researchers in time. The paper also points an important question about the contents of modern education at the secondary school and higher levels.